Ciprofloxacin-resistant enterobacteria harboring the aac(6′)-Ib-cr variant isolated from feces of inpatients in an intensive care unit in Uruguay - Cordeiro, Nicolás F. (2008)
The presence of aac(6′)-Ib-cr is associated with decreased susceptibility to aminoglycosides (kanamycin, amikacin, and tobramycin) and to norfloxacin and ciprofloxacin (9). This allelic variant of aac(6′)-Ib was found to be linked to the extended-spectrum β-lactamase (ESBL) gene blaCTX-M-15 in isolates from many countries (4, 6, 7), while association of aac(6′)-Ib with the blaCTX-M-2 ESBL gene has been widely reported in Uruguay and Argentina (3, 11).